If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-1+5x=6x-1
We move all terms to the left:
-1+5x-(6x-1)=0
We get rid of parentheses
5x-6x+1-1=0
We add all the numbers together, and all the variables
-x=0
x=0/-1
x=0
| -5(v+5)=-2-31 | | -7u+34=3(u-2) | | 6(x+1)/5=3x-3 | | -2k-8+7=34 | | 2x+9(x+1)=12 | | 6–2x=5x-9x+8 | | -4x-3=-16=-52 | | 9(x+4)=7x+32 | | -16x^2+40x-24=0 | | -4z-3=-16=-52 | | -16x^2+40x-55=0 | | 28=-k+1-2k-9 | | 2x-8=-2x-56 | | 2x(60)=55(12) | | 18x+50=146 | | 9(x+4)=72+32 | | 26(4r-1)=26 | | -20-(-24=x/12 | | 8x+10x=30+4x | | 3c+2=7c | | F(x)=1/5x+1 | | b-4+4b=24 | | -7n-21=-49 | | 7/c+4=35/55 | | -26-5d=-8(7d+9) | | 10(.7)^x+17=38 | | 2x´2–8x–10=32 | | 100+8d=400 | | 8+2x=66 | | 4x=19+3× | | 214×2=f | | (5b-5)(2b-3)=0 |